The Implementation of the Teaching at the Right Level (TaRL) Approach to Improve Cognitive Abilities of the Introduction to Python Topic in Informatics Lessons - Abdul Wafi; Yudhi Christianto; Siti Sendari (Bulletin of Pedagogical Research, 2025)
The Merdeka Curriculum introduces a learning approach known as Teaching at the Right Level (TaRL), a method designed based on students' ability mapping to tailor instruction according to each learner’s specific needs. This study explores the impact of implementing the TaRL approach on students' cognitive development in the topic of Python programming, within the Informatics subject for Class X-4 at SMAN 8 Malang. Employing a Classroom Action Research (CAR) methodology, the research aims to identify classroom challenges and develop effective solutions. The findings demonstrate that using appropriate and well-structured learning strategies significantly enhances students’ learning outcomes. This study contributes meaningfully to the development of differentiated instruction practices in Informatics education, particularly in introducing Python programming. The novelty of this research lies in the application of the TaRL approach within a digital learning context—specifically in Python programming—a relatively unexplored area, as previous studies have predominantly focused on basic literacy and numeracy